2015
DOI: 10.1097/phm.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi and Multimodal Exercise Training on Movement and Balance Function in Mild to Moderate Idiopathic Parkinson Disease

Abstract: This multimodal exercise training could improve motion function and benefit balance function in patients with Parkinson disease. The multimodal exercise training is easy to learn and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 21 publications
4
53
1
4
Order By: Relevance
“…13,15,16,26 Although we did not further examine short-term gait improvements with exercise, we demonstrated improved off medication fast gait velocity at 24 months with both PRE and mFC, which may have been driven by improved cadence without improvement in stride length. The improvements in cadence occurred in all walking conditions in both groups, which is important because temporal gait measures tend to be resistant to medical management in PD.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…13,15,16,26 Although we did not further examine short-term gait improvements with exercise, we demonstrated improved off medication fast gait velocity at 24 months with both PRE and mFC, which may have been driven by improved cadence without improvement in stride length. The improvements in cadence occurred in all walking conditions in both groups, which is important because temporal gait measures tend to be resistant to medical management in PD.…”
Section: Discussionmentioning
confidence: 82%
“…Studies of multimodal balance and core strengthening interventions, similar to the multimodal PD-specific modified Fitness Counts (mFC) exercise program, have been shown to improve gait velocity and spatial gait measures in people with PD. 26,27 We previously reported that both groups improved general physical function and fast walking velocity (25 foot walk test), while off and on medication. 20 However, the long-term positive or differential effects of PRE or mFC on spatial, temporal, or stability-related gait impairments in people with PD were not reported.…”
Section: Introductionmentioning
confidence: 91%
“…Using a meta-analytic approach and incorporating a number of recent clinical trials not included in previous reviews[3741], this study aimed to systematically evaluate and quantify the effects of TCQ on motor and non-motor function and quality of life in patients with PD.…”
Section: Introductionmentioning
confidence: 99%
“…Non-medical Parkinson's disease treatment includes ergotherapy, psychotherapy, physical exercises, individual physical therapy and, if necessary, speech therapy (Zhou, Yin, Gao, & Yang, 2015;Elkins, 2015;Zhang, Hu, Nie, Jin, Chen, Guan, Jin, 2015;Li, & Harmer, 2015;Gavrikova, Masuda, Murakami, Hasegawa, Koike, Kuroha, & Uchiyama, 2011). Medical and surgical treatment helps to reduce Parkinson's disease symptoms, but does not help to restore freedom of movement .…”
Section: Resultsmentioning
confidence: 99%